Implementation of ADDIE in Multimedia to Improve Students' Understanding of Extrapolation - Sofhia Nabilah; Eka Fitrajaya Rahman; Asep Wahyudin (Jurnal Guru Komputer, 2023)
Branching becomes one of the materials in basic programming subjects in vocational schools that have not been properly understood by the student. The observation results showed a problem in the learning process of the subject. The proposed solution to solve the identified problem is develop an interactive learning multimedia. Interactive multimedia helps solve problems by making the subject matter more interesting and easier to understand. This study aims to analyze the implementation of ADDIE model in the design and development of learning, improve student extrapolation understanding, and student response to multimedia. Interactive multimedia has been developed and rated "Feasible" by material experts with a score of 3,67 and is rated "Feasible" by multimedia construction experts with a score of 4,03. The use of multimedia, on the other hand, improves the understanding of student extrapolation shown it is emphasized by using the ANOVA test with a value of 0,553 x 10-130,05. The student's response to interactive multimedia received a score of 4,53 with the category "Very high".